2003
DOI: 10.1001/jama.290.14.1859
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low-Level Ozone and Fine Particles With Respiratory Symptoms in Children With Asthma

Abstract: Context Exposure to ozone and particulate matter of 2.5 µm or less (PM 2.5 ) in air at levels above current US Environmental Protection Agency (EPA) standards is a risk factor for respiratory symptoms in children with asthma.Objective To examine simultaneous effects of ozone and PM 2.5 at levels below EPA standards on daily respiratory symptoms and rescue medication use among children with asthma.Design, Setting, and Participants Daily respiratory symptoms and medication use were examined prospectively for 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
241
1
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(263 citation statements)
references
References 22 publications
8
241
1
9
Order By: Relevance
“…Ambient ozone is formed from the photochemical reaction of nitrogen oxides found in traffic related pollutants and tends to be highest in the late afternoon. Several studies have shown a causal relationship between O 3 exposure and respiratory-tract symptoms, decreased lung function, and asthma exacerbations (Gent et al, 2003;Kinney et al, 1996). Exposure to O 3 levels below 60 ppb has been shown to affect lung function in amateur cyclists, and it has been speculated that childhood exposure may have detrimental effects on lung function later in life (Galizia & Kinney, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient ozone is formed from the photochemical reaction of nitrogen oxides found in traffic related pollutants and tends to be highest in the late afternoon. Several studies have shown a causal relationship between O 3 exposure and respiratory-tract symptoms, decreased lung function, and asthma exacerbations (Gent et al, 2003;Kinney et al, 1996). Exposure to O 3 levels below 60 ppb has been shown to affect lung function in amateur cyclists, and it has been speculated that childhood exposure may have detrimental effects on lung function later in life (Galizia & Kinney, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Downs et al [65] demonstrated that declines in PM 10 concentration may actually lead to an attenuated decline in lung function in adult patients. However, research on healthy adults has not as consistently shown an association between PM and respiratory compromise [66].…”
Section: Pm and Pulmonary Functionmentioning
confidence: 99%
“…PM2.5 concentration has been found to be associated with cardiopulmonary disease, lung cancer, and an increased morbidity and mortality (Schwartz et al, 1996;Gent et al, 2003Gent et al, , 2009Dominici et al, 2006;Bell et al, 2007;Franklin et al, 2007;Slama et al, 2007;Pope et al, 2002;Miller et al, 2007;Lepeule et al, 2012). As an official norm to stand for fine-particle abundance, PM2.5 mass concentrations are monitored widely by the US Environmental Protection Agency (EPA) through in situ instruments at surface monitoring sites.…”
Section: Introductionmentioning
confidence: 99%